2008
DOI: 10.3168/jds.2007-0893
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and Utilization of Trans Octadecenoic Acids in Lactating Dairy Cows

Abstract: Trans fatty acids (FA) arise in ruminant-derived foods as a consequence of rumen biohydrogenation and are of interest because of their biological effects and potential role in chronic human diseases. Our objective was to compare 2 trans FA, elaidic acid (EA; trans-9 18:1) and vaccenic acid (VA; trans-11 18:1), with oleic acid (OA; cis-9 18:1) relative to plasma lipid transport and mammary utilization for milk fat synthesis. Three ruminally cannulated, Holstein dairy cows, 259 +/- 6 DIM (mean +/- SEM), were ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
34
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 37 publications
8
34
3
Order By: Relevance
“…Studies involving incubations with rat liver microsomes demonstrated that isomers of trans 18:1 with double bonds at D4 to 7 and D11 to 15 but not D8 to 10 can serve as substrates for SCD in vitro with the extent of conversion being dependent on double-bond position (Mahfouz et al, 1980;Pollard et al, 1980) with the implication that trans-8 18:1, trans-9 18:1 and trans-10 18:1 are not desaturated in the ruminant mammary gland. Although post-ruminal infusions of trans-9 18:1 (Rindsig and Schultz, 1974;Tyburczy et al, 2008) have been shown to have no effect on lipogenesis in the lactating cow, under the specified conditions of these experiments the supply of 18:0 at the mammary gland remained unchanged, and therefore these observations do not provide a rigorous test of the possible role of lowered milk fat fluidity in the etiology of diet-induced MFD. Short-term abomasal infusions of sterculic oil (Griinari et al, 2000;Corl et al, 2001;Kay et al, 2004), trans-9, trans-11 CLA (Perfield et al, 2007) and trans-10, trans-12 CLA (Saebø et al, 2005b;Perfield et al, 2006) as well as administration of Co-EDTA in the rumen (Shingfield et al, 2006b and Figure 6 Structural features of trans fatty acids known to be associated with anti-lipogenic activity in a range of biological models.…”
mentioning
confidence: 77%
“…Studies involving incubations with rat liver microsomes demonstrated that isomers of trans 18:1 with double bonds at D4 to 7 and D11 to 15 but not D8 to 10 can serve as substrates for SCD in vitro with the extent of conversion being dependent on double-bond position (Mahfouz et al, 1980;Pollard et al, 1980) with the implication that trans-8 18:1, trans-9 18:1 and trans-10 18:1 are not desaturated in the ruminant mammary gland. Although post-ruminal infusions of trans-9 18:1 (Rindsig and Schultz, 1974;Tyburczy et al, 2008) have been shown to have no effect on lipogenesis in the lactating cow, under the specified conditions of these experiments the supply of 18:0 at the mammary gland remained unchanged, and therefore these observations do not provide a rigorous test of the possible role of lowered milk fat fluidity in the etiology of diet-induced MFD. Short-term abomasal infusions of sterculic oil (Griinari et al, 2000;Corl et al, 2001;Kay et al, 2004), trans-9, trans-11 CLA (Perfield et al, 2007) and trans-10, trans-12 CLA (Saebø et al, 2005b;Perfield et al, 2006) as well as administration of Co-EDTA in the rumen (Shingfield et al, 2006b and Figure 6 Structural features of trans fatty acids known to be associated with anti-lipogenic activity in a range of biological models.…”
mentioning
confidence: 77%
“…Trans-11 18:1 absorbed in the small intestine is preferentially incorporated into plasma triacylglycerols (Tyburczy et al, 2008;Halmemies-Beauchet-Filleau et al, 2013a) that serve as a substrate for milk fat synthesis (Shingfield et al, 2010). Such a mechanism explains the relatively high apparent transfer from the gut into milk and increases in milk fat trans-11 18:1 and cis-9,trans-11 CLA concentrations to increases in postruminal trans-11 18:1 supply (Tyburczy et al, 2008;Halmemies-Beauchet-Filleau et al, 2013a).…”
mentioning
confidence: 89%
“…Such a mechanism explains the relatively high apparent transfer from the gut into milk and increases in milk fat trans-11 18:1 and cis-9,trans-11 CLA concentrations to increases in postruminal trans-11 18:1 supply (Tyburczy et al, 2008;Halmemies-Beauchet-Filleau et al, 2013a). Milk fat total CLA concentration typically varies between 0.3 and 0.5 g/100 g of total FA (Lindmark-Månsson, 2008), but on diets supplemented with fish oil or high amounts of plant oil, enrichment of CLA can approach 3.6 g/100 g of total FA .…”
mentioning
confidence: 99%
“…According to Shingfield and Wallace (2014), unsaturated FA with chain lengths >18-C are susceptible to extensive ruminal biohydrogenation. In addition to ruminal biohydrogenation, n-3 FA are extensively confined to plasma cholesterol ester and phospholipids (Tyburczy et al, 2008), which are poorly taken up by the mammary gland (Offer et al, 2001).…”
Section: Milk Fa Profilementioning
confidence: 99%